(untitled) (Fiep Bulletin - online, 2017)
With Law No. 10,639 and its 2003 redesign, the Law No. 11,645 of 2008 became compulsory education not only ofhistory but also of african-Brazilian culture in elementary and middle school. Seeking to present this culture through play, games,dances, sports and struggles of black origin or valued by this population, was born this research, with the goal of checking how willthe Black Body Culture is discussed in Physical Education from the initial series Elementary School I. For this, an analysis wasmade from the literature on athematic, which showed that no one speaks of Body Culture Black full with students from elementaryschool, but only piecemeal in content categories: game, game, fight , dance, body expression.